INTEGRATED MANAGEMENT OF WILT COMPLEX INVOLVING MELOIDOGYNE INCOGNITA AND RALSTONIA SOLANACEARUM ON BRINJAL (SOLANUM MELONGENA L.) - S. PAVITHRA; RAHEESA KHATIB (The Bioscan, 2014)
An experiment was conducted in the farm of the Department of Plant Pathology, GKVK, Bangalore to test the effect of different treatments on management of wilt complex of brinjal under local conditions. Among different treatments tested Integration of mustard as an intercrop, streptocycline and COC were found superior against Meloidogyne incognita and Ralstonia solanacearum wilt complex in brinjal under field conditions. Among the treatments tested to manage wilt complex under field condition, mustard intercrop + streptocycline @ 0.5 g/lit + COC 50% WP (1g/lit) reduced bacterial wilt incidence (23.35%). It recorded 63.33 galls/root system which accounted to 72.54 per cent reduction over control and recorded an yield of 1.92 kg/25 m2 followed by mustard intercrop + P. fluorescens @ 20g/m2 (1×108 ) which was effective in reducing wilt by 28.35 per cent. It recorded 51.66 galls/root systems which accounted to 77.60 per cent reduction over control and recorded yield of 1.78 kg/ 25 m2